A new chaos-based image encryption algorithm with dynamic key selection mechanisms - Chai, Xiuli; Yang, Kang; Gan, Zhihua (Multimedia tools and applications, 2017)
In recent years, a wide variety of cryptographic algorithms based on chaos have been put forward and most of them have been proved to be successful by adopting the traditional permutation-diffusion architecture. However, one drawback these methods mostly hold is that they have little connection with the plaintext or, properly speaking, the relationship between them is rather less. The drawback makes the encryption algorithms vulnerable to the known-plaintext and chosen-plaintext attack. In addition, the secret keys are stationary at most times, and they can’t be selected dynamically by the corresponding plain image pixels. In order to overcome these disadvantages mentioned above, we introduce a new chaos-based image encryption algorithm with dynamic key selection mechanisms in this paper, and present a dynamic keystream sequence group selection mechanism (DKSGSM) and a dynamic keystream selection mechanism (DKSM). They strongly enhance the relationship between the plaintext and the encryption scheme. In particular, the DKSGSM and DKSM expand the selection range of the keys and allow us to select the keys dynamically by the corresponding plaintext pixels. What’s more, by adopting the bidirectional encryption, we can spread the influence to the whole image once a tiny change in plain image and this can greatly increase the security level of our encryption method. Simulation results and numerical analyses indicate that our encryption scheme is safe and efficient.